In-plane dynamic crushing of a novel circular-celled honeycomb nested with petal-shaped mesostructure. (15th October 2019) - Yang, Xianfeng; Xi, Xulong; Pan, Qifan; Liu, Hu
Abstract: Honeycomb structures have attracted much attention in various engineering fields due to its superiorities in high specific strength, high specific stiffness and excellent energy-absorbing characteristics. The light-weight materials with exceptional mechanical behaviors can be achieved by incorporating the reinforced mesostructure into the regular honeycomb structures. In the present work, a novel circular-celled honeycomb was proposed by incorporating the petal-shaped mesostructures into the regular circular cell honeycomb. The 3D finite element models of the petal-shaped honeycombs (PSH) are established to investigate the in-plane crushing behavior and energy absorption capacity under different impact velocities through the nonlinear finite element code LS-DYNA. A comparison between the regular circular-cell honeycomb, the single petal nested circular honeycomb and the PSH was carried out, and the simulation results indicated that the PSH exhibited the best mechanical behavior and energy absorption characteristics compared with the other two types of honeycombs. Three representative deformation modes, namely quasi-static, transition and dynamic mode, were observed from the numerical simulations of the PSH with different geometric configurations and impact loadings, and the failure mode map was also summarized to furtherly clarify the localized deformation characteristics. In addition, the influences of impact velocity and the relative density on the plateau stress and the energy absorption behavior of the PSH were also investigated in this paper. The results showed that the specific energy absorption of PSH can be improved by up to nearly twice than the regular circular honeycomb under the same impact speed.